Expression of galectin-3 in adenoid cystic carcinoma & mucoepidermoid carcinoma of salivary glands- a study from Pakistan - Hussain, Sunila; Rashid Siraj, Muhammad; Anjum, Rabia; Qureshi, Ihtesham-ud-Din; Nagi, A H; Naseem, Nadia (International Journal of Dental Research, 2017)
Background: Adenoid cystic carcinoma (AdCC) and mucoepidermoid carcinoma (MEC) are the commonest salivary gland malignancies in Pakistan constituting almost 75% of all malignant salivary gland tumours.Objective: The objective of this study was to determine the expression of galectin-3 (Gal-3) in AdCC and MEC of salivary glands and to see its relationship with histological differentiation in these tumours.Method: This descriptive study was conducted at the Department of Morbid Anatomy and Histopathology/ Oral Pathology, University of Health Sciences Lahore, Pakistan. Biopsies and detailed clinical data of 20 cases each of adenoid cystic carcinoma and mucoepidermoid carcinoma reported at local tertiary care hospitals from Jan. 2014 to Sep. 2015 were retrieved. The histologic diagnosis was made on Hematoxylin and Eosin staining. The tumours were graded into grades I, II & III according to the most recent grading criteria. AdCC was studied with respect to its morphological patterns (tubular, cribriform and solid) while MEC was studied with special concern to the cell types seen in it (mucous, intermediate, squamous and clear cells). Immunohistochemical expression of galectin-3 was determined in these tumours with respect to histological grades, patterns and cell types seen.Results: Moderate positivity (55%) for anti-galectin-3 antibody was the most frequently observed score for galectin-3 in both MEC and AdCC. Moderate positive (55%) staining reaction was followed by weak positive (30%) staining reaction in AdCC. Total score for antigalectin-3 antibody, positive stromal reaction (intensity) and location of cellular signals for anti-galectin-3 antibody were all found to be significantly associated with grades of AdCC. Also, histological pattern of AdCC (tubular, cribriform and solid) were significantly associated with type of anti-galectin-3 staining pattern of cells (p<0.001). In MEC, moderate positive (55%) staining for anti-galectin-3 antibody was followed by strong positive reaction (30%). The total score for anti-galectin-3 antibody was significantly associated with grades of the tumour and lymph node status. Also, the type of staining reaction in cells was significantly associated with cell type (mucous, squamous and intermediate cells).Conclusion: It can be concluded from the current study that expression of Gal-3 decreases with decreasing differentiation in parenchyma of malignant tumours while its expression in tumour extracellular environment increases with increasing grade of the tumour.Also, it can be concluded that nuclear expression of Gal-3 is associated tumour differentiation and cytoplasmic expression with tumour cell proliferation.